Comparison of RT-qPCR With Branched DNA to Quantify a Lipid Nanoparticle–Encapsulated mRNA Therapeutic in Serum and Liver Tissue Samples From Nonclinical PK Studies - Jessica Ortiz; Laura Brunner; Lei Ci; Rena Baek; Darshana Jani; Jean-Claude Marshall; Jason Pennucci (The AAPS Journal, 2025)

Evaluating the shelf life of strawberries using a portable Vis-NIR spectrophotometer and a Reflectance Quality Index (RQI) - Laura Rabasco-Vílchez; Francisco Jiménez-Jiménez; Arícia Possas; Matthias Brunner; Christian Fleck; Fernando Pérez-Rodríguez (Postharvest Biology and Technology, 2024)

Emydomyces testavorans DNA is detected from shell swabs of companion chelonians - Timothy J. Brunner; Amanda D. Wong; Laura Adamovicz; Amber Simmons; Emilie Ospina; Krista A. Keller (Journal of Exotic Pet Medicine, 2024)

An outbreak of type C botulism in free-ranging Southern lapwing (Vanellus chilensis) - Igor Ribeiro dos Santos; Jacqueline Raiter; Carolina Buss Brunner; Franciéli Adriane Molossi; Luan Cleber Henker; Tainah Pereira Dal Pont; Laura Junqueira de Camargo; Raquel Silva Alves; Cláudio Wageck Canal; Andressa da Silva Martins; Tamires Ataides Silva; Ana Carolina Borsanelli; et al. (Veterinary Research Communications, 2024)

The actors of the Swiss plastic system: An analysis of beliefs and interests - Laura Gatto; Dunia Brunner; Pirmin Bundi; Stéphane Nahrath (Journal of Cleaner Production, 2023)

Cellular Distribution Pattern of tjp1 (ZO-1) in Xenopus laevis Oocytes Heterologously Expressing Claudins - Nora Brunner; Laura Stein; Salah Amasheh (The Journal of Membrane Biology, 2023)
Epithelial barriers constitute a fundamental requirement in every organism, as they allow the separation of different environments and set boundaries against noxious and other adverse effectors. In many inflammatory and degenerative diseases, epithelial barrier function is impaired because of a disturbance of the paracellular seal. Recently, the Xenopus laevis oocyte has been established as a heterologous expression model for the analysis of transmembrane tight junction protein interactions and is currently considered to be a suitable screening model for barrier effectors. A prerequisite for this application is a physiological anchoring of claudins to the cytoskeleton via the major scaffolding protein tjp1 (tight junction protein 1, ZO-1). We have analyzed the oocyte model with regard to the interaction of heterologously expressed claudins and tjp1. Our experiments have revealed endogenous tjp1 expression in protein and mRNA analyses of unfertilized Xenopus laevis oocytes expressing human claudin 1 (CLDN1) to claudin 5 (CLDN5). The amphibian cell model can therefore be used for the analysis of claudin interactions. Graphical Abstract

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Validation of a Ligand Binding Assay Using Dried Blood Spot Sampling - Daniel Burns; Laura Brunner; Surendran Rajendran; Beth Johnson; Mark Ma; Jin Wang (The AAPS Journal, 2013)

Scenarios of Waste Management for a Waste Emergency Area - Maria Laura Mastellone; Paul H. Brunner; Umberto Arena (Journal of Industrial Ecology, 2009)
Summary In the Campania region, an area in the south of Italy with 5.7 million inhabitants and a production of about 7,900 tonnes of municipal solid waste per day, an emergency situation was created by inappropriate waste management policy and practice. In order to support decisions regarding future solutions for this crisis, reliable, transparent, and impartial strategies and concepts are needed. For this purpose, six waste management scenarios have been defined and quantitatively assessed by means of substance flow analysis (SFA). The scenarios are based on firm objectives and recent legislation for waste management and take into account regional waste production and composition as well as existing waste treatment infrastructure. They are evaluated and compared with the status quo in view of reaching the goals of waste management. For each scenario, the following material flows were quantified: wastes that would be sent to different processes, such as those of mechanical‐biological treatment, incineration, or anaerobic digestion; treatment residues (in mass and volume) to be diverted to landfills; materials recoverable by recycling processes; and energy obtainable by waste‐to‐energy and anaerobic digestion plants. The results demonstrate that a future waste management system that is based on a combination of more recycling, thermal treatment, anaerobic digestion, and improved landfilling reaches the objectives of waste management much more closely than the present, inadequate system.

“Fit-for-Purpose” Method Validation and Application of a Biomarker (C-terminal Telopeptides of Type 1 Collagen) in Denosumab Clinical Studies - Jin Wang; Jean Lee; Daniel Burns; David Doherty; Laura Brunner; Mark Peterson; Binodh DeSilva (The AAPS Journal, 2009)